2013
DOI: 10.4025/actascitechnol.v35i3.13176
|View full text |Cite
|
Sign up to set email alerts
|

<b>Sensory analysis and chemical characterization of cereal enriched with grape peel and seed flour</b> - doi: 10.4025/actascitechnol.v35i3.13176

Abstract: ABSTRACT. Current study analyzes a breakfast cereal with partial replacement of corn grits by the flour of grape seeds and peels from the residues of the wine industry. Residues (peels and seeds) of grape varieties 'Isabel' and 'Bordô' were dried in an air circulation oven at 85°C for 6 hours to obtain the flour. Three formulations of breakfast extruded cereals were prepared with 10, 15 and 20% of grape flour to replace corn grits. The formulas were analyzed with regard to their phenolic compounds, fibers, ins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
7

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 10 publications
0
7
0
7
Order By: Relevance
“…Deng, Penner, and Zhao () found different anthocyanins’ concentrations in red grape skins: Merlot (1.42 mg Mal‐3‐glu/g db), Cabernet Sauvignon (0.89 mg Mal‐3‐glu/g db), and Pinot Noir (0.29 mg Mal‐3‐glu/g db). TPC and total anthocyanins of grape pomace vary according to grape variety, maturation degree, and processing method (Oliveira, Marques, Kwiatkowski, Monteiro, & Clemente, ). The results obtained in this study showed that GPF still presents relatively high TPC and anthocyanins that were not extracted in the industrial processing of grape juice.…”
Section: Resultsmentioning
confidence: 99%
“…Deng, Penner, and Zhao () found different anthocyanins’ concentrations in red grape skins: Merlot (1.42 mg Mal‐3‐glu/g db), Cabernet Sauvignon (0.89 mg Mal‐3‐glu/g db), and Pinot Noir (0.29 mg Mal‐3‐glu/g db). TPC and total anthocyanins of grape pomace vary according to grape variety, maturation degree, and processing method (Oliveira, Marques, Kwiatkowski, Monteiro, & Clemente, ). The results obtained in this study showed that GPF still presents relatively high TPC and anthocyanins that were not extracted in the industrial processing of grape juice.…”
Section: Resultsmentioning
confidence: 99%
“…Oliveira et al [54] conducted a study investigating the partial substitution of corn grits by grape waste flour (peels and seeds) using the 9-point Hedonic Scale for checking the acceptance, and discovered a better acceptance for the formulations containing, 15% and 20% (in order of preference), which also offered the highest fibre content. Another investigation of grape waste flour (peels) showed that the Global Acceptance Test disclosed that the extrudate containing 5% of this flour had better acceptance than the control formulation and the 10% formulation (regarding the texture parameter), and was not different from the control formulation in terms of flavour [55].…”
Section: Sensory Analysis Of Cake Formulationsmentioning
confidence: 99%
“…In order to analyze the experimental texture a Stable Micro Systems Texture Analyzer TAXT2i (Texture Technologies Corp, England) was used as described by Oliveira [19].…”
Section: Methodsmentioning
confidence: 99%